AN INTEGRATED ECONOMETRIC MODEL FOR ASSESSING THE INNOVATIVE DEVELOPMENT OF DEHKAN FARMS - Ergashov Yashnarbek Istam ogli, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. This paper develops an integrated econometric model to assess the level of innovative development of dehkan farms and to examine its impact on economic performance. An Innovation Development Index (IDI) is constructed by aggregating technological, institutional, financial, and human capital indicators using a standardized weighting approach. Panel data econometric techniques, including fixed and random effects models, are employed to evaluate the relationship between innovation and farm income. The empirical results reveal a statistically significant and positive effect of innovation on farm performance, confirming that innovation-driven development plays a crucial role in enhancing the competitiveness and sustainability of small-scale agricultural producers. The findings provide important policy implications for innovation-oriented agricultural development strategies in emerging economies.